GAMBARAN SOSIAL EKONOMI, PENDIDIKAN IBU DAN POLA PEMBERIAN MAKAN BALITA STUNTING DI WILAYAH KERJA PUSKESMAS DAPET KECAMATAN BALONGPANGGANG - Ihda Sholihatun Nisa'; Dra Eka Srirahayu Ariestiningsih; Desty Muzarofatus Sholikhah (Universitas Muhammadiyah Gresik, 2022)
Stunting is a form of malnutrition which is characterized by an indicator of height according to age.The purpose of this study was to determine the socio-economic description, mother's education and feeding patterns to stunting toddlers in the Dapet Health Center work area, Balongpanggang District. This research method is descriptive observational. The population in this study was 90 stunting toddlers who were taken by purposive sampling technique. The independent variables in this study were socioeconomic, maternal education and feeding behavior. The dependent variable in this study is stunting. Collecting data using a questionnaire. Analysis of the data used is univariate analysis. The results of the study with 71 samples showed that as many as 98.6% of toddlers who experienced short stunting and 1.4% of toddlers who experienced very short stunting. The socioeconomic status of stunting toddlers is less than the Gresik Regency UMK 70.5%, more than the Gresik Regency UMK 29.5%. Low maternal education for stunting toddlers 56.3%. Stunting toddlers with high maternal education 43.6%. The feeding pattern of stunting toddlers is seen from exclusive breastfeeding, complementary feeding, feeding frequency, feeding size, feeding texture, feeding variations, food processing methods.